Determining Effective Components in Citizen Participation in the form of Social Trap Theory and The Bystander Effect (Case Study :Mashhad) - Rostam Saberifar; Ezat Hoseini (جغرافیا و آمایش شهری منطقه‌ای, 2022)
In this study, with emphasis on financial participation, which is considered the most complex type of participation, it was tried to analyze the factors affecting the participation of citizens of Mashhad by using the social trap theory and the spectator effect. For this purpose, the basic factors affecting the payment of renovation and car tolls were determined and the effect of each of them was evaluated. The research method was descriptive and analytical and the required data was obtained from a sample of 300 people in the form of two groups of participants and non-participants. The collected data were analyzed using analysis of variance and t-test with two independent groups. The results showed that the attitudes of participants and non-participants were different in relation to the effective factors, and the highest effect was related to the awareness of the behavior of the municipal personnel and the person's relatives, as well as his moral conscience in relation to paying tolls. In this process, the trust or lack of trust in the capability of the municipal personnel and also the type of orientation of the city council members (reformist or fundamentalist) had no obvious effect on the payment of tolls. According to this finding, aimless advertisements and providing incentives do not have much place in people's participation and the solution is the formation and expansion of social capital.